Green Vehicles' Responses to an Expiring Congestion Toll Exemption: Findings from a Natural Experiment in Stockholm, Sweden - Fatemeh Naqavi; Emma Engström; Joel P. Franklin (Findings)
Stockholm established time-varying congestion pricing in 2007, and adopted a toll exemption as a temporary incentive for green vehicles (GVs) that ended in 2012. We examine the behavioral effects of phasing out the exemption by studying the change in cordon crossing events for GV morning commuters between May 2012 and May 2013, with a random sample of conventional vehicles (CVs) as control. The results suggest i) a significant drop in the total number of crossings; ii) a slight shift towards later journeys in the morning; and iii) a reduction in the ratio of peak-toll period crossings to other ones.